PERANCANGAN E-COMMERCE PEMASARAN KAIN SONGKET SILUNGKANG BERBASIS WEB - Phooja Sakhena; Titi Sriwahyuni; Muhammad Adri (Universitas Negeri Padang, 2019)
E-Commerce is a process of buying, selling or exchanging goods / products, services and information obtained through a computer network. Web-based marketing of songket silungkang cloth e-Commerce is an online product sales website that contains songket silungkang fabric products. This application can be used by songket silungkang craftsmen. E-Commerce is designed using the PHP programming language with the CodeIgniter framework and database using MySql Xampp. E-Commerce marketing of songket silungkang fabric produces a web-based design of songket silungkang marketing E-Commerce that can be used by the general public to buy songket silungkang products. The marketing e-commerce of silungkang songket cloth contains the products of woven songket from the residents of Silungkang. E-Commerce songket silungkang fabric can be used as a medium to promote songket silungkang fabric and make it easier for buyers to know the information on songket silungkang woven products and make it easier to make transactions with weaving craftsmen. Keywords: Web-based Silungkang Songket Fabric Marketing E-Commerce, E-Songket